Cross-cultural adaptatiion and validation of the stroke specific quality of life 2.0 scale into Hausa language - Odetunde, Marufat O. (J Patient Rep Outcomes, 2018)
BACKGROUND: The Stroke Specific Quality of Life 2.0 (SS-QoL 2.0) is a widely used scale that has been cross-culturally adapted to many languages including Yoruba, one of the three major Nigerian languages. Non-availability of SS-QoL 2.0 in Hausa, the indigenous language of Northern Nigeria has restricted its use in Hausa stroke-survivors (SSV). This study was aimed at cross-culturally adapting SS-QoL 2.0 to Hausa and assessing validity and reliability of the Hausa version. The English version of SS-QoL 2.0 was cross-culturally adapted to Hausa following the American Association of Orthopaedic Surgeons’ guideline. A final Hausa version (FHV) was produced through forward and back-translations, expert committee review, pretesting and cognitive debriefing interview. The FHV was investigated for test-retest reliability, internal consistency, convergent, construct and known-group validity on 86 consenting Hausa SSV. Hausa version of WHOQoL-BREF was used to assess convergent validity (n = 57) while English versions of SS-QoL was used to assess construct validity (n = 51) of FHV. The FHV was re-administered on 53 of the participants at 7-day interval to assess test-retest reliability. Each scale was administered in random order to eliminate bias. Data were analysed using Spearman correlation, Cronbach’s alpha, Intra-class Correlation Coefficient (ICC), Independent t-test and One-way ANOVA at p < 0.05. RESULTS: The SS-QoL 2.0 was successfully cross-culturally adapted to Hausa. Participants’ mean overall score on SS-QoL 2.0 (145.30 ± 39.78) did not differ significantly from that of FHV (150.41 ± 40.45) p = 0.28. The mean domains score did not differ significantly except in self-care and work domains. There were weak to good correlations for 6 out of 8 similar domains on Hausa versions of SS-QoL and WHOQoL-BREF (r = 0.21–0.61; p = 0.001–0.006); and good to excellent correlations between Hausa and English versions of SS-QoL (r = 0.70–0.92; p = 0.001). The FHV showed high to excellent test-retest reliability (ICC = 0.86–0.99) and acceptable to excellent internal consistency (Cronbach’s α = 0.71–0.90). No significant gender differences were demonstrated for any domains of FHV and for most domains across age groups. CONCLUSION: The FHV is valid and reliable. The scale is recommended for assessing health-related quality of life among Hausa stroke survivors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41687-018-0082-1) contains supplementary material, which is available to authorized users.